EFEKTIVITAS PEMBERLAKUAN ASEAN-CHINA FREE TRADE AREA (ACFTA) TERHADAP PASAR INDUSTRI KOSMETIK INDONESIA - Wezi Tresia O; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research was made to explain how the effectiveness of Enforcement ASEAN-China Free Trade Area (ACFTA) to Cosmetic Industry Market Indonesia. The trend of free trade that occurs at this time, resulting in each participating country to economic progress. ACFTA trade cooperation is the cooperation of the decrease or elimination of tariffs to reduce losses from the application of higher taxes in order to increase the trading volume of each stakeholder.The research method use is a descriptive of qualitative analysis research method about fact . The interpretation of the data and draw conclusions made with reference to the concepts and theoretical literature references according to research problems that have been formulated previously.The conclution of this research indicate that the application of an ASEAN-China Free Trade Area (ACFTA) has been effective against Indonesian cosmetics industry market. Deletion or the removal of tariff and non tariff has opened up great opportunities for international trade. This collaboration has also opened access to markets cosmetic products in Indonesia. The investment climate is increasing. The creation of a competitive investment regime and open the opportunity for Indonesia to attract more investment from China. Also create new jobs on the results of economic cooperation and development undertaken by Chinese companies in Indonesia.Key words: ACFTA, Cosmetics, Cooperation, Free Trade Zone